2022
DOI: 10.1097/ico.0000000000003058
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Standard Corneal Cross-Linking Procedures Performed With Short Versus Standard Riboflavin Induction: A Save Sight Keratoconus Registry Study

Abstract: Purpose:The objective of this study was to compare the effectiveness and safety of short versus standard riboflavin induction times in cross-linking (CXL) for keratoconus.Methods:A retrospective comparative study was conducted with data from the Save Sight Keratoconus Registry. Inclusion criteria were epithelium-off technique, standard UVA CXL protocol (3 mW/cm2 for 30 minutes), riboflavin induction for 15 minutes (short) or 30 minutes (standard), and 1 year of follow-up data after CXL. Outcome measures includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Nevertheless, our previous study showed that the outcomes in children were comparable to those of adults in the SSKR population. 41 Similarly, we showed that the outcomes with the Dresden (standard) and accelerated UVA protocols, 42 and the CXL procedures with standard and accelerated riboflavin induction times 38 were comparable.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Nevertheless, our previous study showed that the outcomes in children were comparable to those of adults in the SSKR population. 41 Similarly, we showed that the outcomes with the Dresden (standard) and accelerated UVA protocols, 42 and the CXL procedures with standard and accelerated riboflavin induction times 38 were comparable.…”
Section: Discussionmentioning
confidence: 82%
“…36,37 Only epithelium-off CXL procedures were included in this study to align with the most common clinical practice and protocol characteristics varied. These included intra-operative factors such as riboflavin type used, soaking duration, 38 UV-light power and duration, 27 as well as post-operative factors such as the use of bandage contact lenses post-op and topical steroid or antibiotic choice and course duration. Monitoring heterogeneity included keratometry and pachymetry measurement devices, which are known to have limitations in inter-device comparability.…”
Section: Discussionmentioning
confidence: 99%
“…10,21 One of the main treatments tracked by the registry is corneal cross-linking. 10,11 Patient-reported outcomes in the registry are collected using the Keratoconus Outcomes Research Questionnaire (KORQ) 22,23 and the Impact of Vision Impairment (IVI) questionnaire. 5,24 Our previous study 3 found that these 2 questionnaires are the best patient-reported outcome measures for use in people with keratoconus, and we have previously validated them [tested for psychometric properties (including response category functioning, unidimensionality, Rasch model fit statistics, targeting of persons and items, and measurement invariance), validity (known-group validity, concurrent validity), and reliability (internal consistency, Rasch person, and item reliability)] in the SSKR populations 5,22 consistent with the FDA guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the studies evaluating the outcomes of corneal cross-linking are focused on clinical evaluation such as visual acuity, refraction, keratometry, and pachymetry assessments. 8,10,11 There are only a few studies that have looked into the patient-reported QoL outcomes of cross-linking for keratoconus which are further limited by low sample size or the use of poor-quality tools and methods. 1,3,12–15 Regulatory groups such as the US Food and Drug Administration (FDA) 16 recommend evaluating patient-reported outcomes as a part of a comprehensive outcome assessment.…”
mentioning
confidence: 99%
“…1 In the early and intermediate stages, visual correction may be achieved through spectacles or contact lenses, with surgical procedures, such as corneal cross-linking (CXL), used to slow or halt disease progression. 2,3 Despite such interventions, keratoconus may continue to progress and can reduce VA and function, 4 with advanced cases often ultimately requiring corneal transplantation as the definitive treatment. 5…”
mentioning
confidence: 99%